PENGEMBANGAN BAHAN AJAR GEOGRAFI PADA KOMPE-TENSI DASAR MEMAHAMI ATMOSFER DAN DAMPAKNYA TERHADAP KEHIDUPAN DI MUKA BUMI KELAS X SMA/MA SEMESTER II DENGAN MENGGUNAKAN PENDEKATAN KERUANGAN - Yulian Widya Saputra (Jurnal Pendidikan Geografi, 2015)
Abstract: Learning materials geography for class X SMA/MA semester II on basic competence to understand the atmosphere and their impact on life in the face of the earth, in the field there are still many aspects of problems encountered data/facts, concepts, the truth of the representation of an image, generalization, punctuation, readability of the material, the connectedness of formal and material objects, and the use of spatially approach. This research was designed using Dick and Carey model development. This model is modified from the ten steps into five steps. The simplify method or step development model Dick and Carey because this model is based intructional to adopted into development learning material geography. These materials before testing validated by expert lecturers. Validator content rate in terms of suitability of materials with atmospheric approach spatially. In addition to expert assessment material learning of geography experts also conducted to assess product design learning geography in order to make text more quality. Implementation of a validation expert material lasts three times atmospheric validation stages while the expert instructional design geography takes five times the validation stage. Types of data collected during the test run is a description of the results of the work of students in the matter of the test materials of text understanding atmosphere. The structure to  understanding model IRI (Informal Reading Inventory) next to procentase and matched with answer keys. The student's understanding model test is performed three times the IRI of meeting learning. Based on the results of processing the test model can be described understanding IRI that test results the first IRI models of understanding the overall results of 84.5%, model understanding test results both the overall result of 85,3%, test results and an understanding of the overall results of the third model of 91.6%. Recomendation to development learning material geography into next period is the way: (1) to produced product very quality reaasonable to many standar competence of geography, (2) the testing material reasonable to many shcool to  have a good answer abaout development learning material geography, (3) is to reasonable to tes the product into experiment research, and (4) to have a good quality product and comprehenship is to reasonable research multiply years.Keywords: development, learning materials geography, Dick and Carey model, spatially approach.